A narrative review of exercise participation among adults with prediabetes or type 2 diabetes: barriers and solutions - Thielen, Samantha C.; Reusch, Jane E. B.; Regensteiner, Judith G. (Frontiers in Clinical Diabetes and Healthcare, 2023)
Type 2 diabetes (T2D) has been rising in prevalence over the past few decades in the US and worldwide. T2D contributes to significant morbidity and premature mortality, primarily due to cardiovascular disease (CVD). Exercise is a major cornerstone of therapy for T2D as a result of its positive effects on glycemic control, blood pressure, weight loss and cardiovascular risk as well as other measures of health. However, studies show that a majority of people with T2D do not exercise regularly. The reasons given as to why exercise goals are not met are varied and include physiological, psychological, social, cultural and environmental barriers to exercise. One potential cause of inactivity in people with T2D is impaired cardiorespiratory fitness, even in the absence of clinically evident complications. The exercise impairment, although present in both sexes, is greater in women than men with T2D. Women with T2D also experience greater perceived exertion with exercise than their counterparts without diabetes. These physiological barriers are in addition to constructed societal barriers including cultural expectations of bearing the burden of childrearing for women and in some cultures, having limited access to exercise because of additional cultural expectations. People at risk for and with diabetes more commonly experience unfavorable social determinants of health (SDOH) than people without diabetes, represented by neighborhood deprivation. Neighborhood deprivation measures lack of resources in an area influencing socioeconomic status including many SDOH such as income, housing conditions, living environment, education and employment. Higher indices of neighborhood deprivation have been associated with increased risk of all-cause, cardiovascular and cancer related mortality. Unfavorable SDOH is also associated with obesity and lower levels of physical activity. Ideally regular physical activity should be incorporated into all communities as part of a productive and healthy lifestyle. One potential solution to improve access to physical activity is designing and building environments with increased walkability, greenspace and safe recreational areas. Other potential solutions include the use of continuous glucose monitors as real-time feedback tools aimed to increase motivation for physical activity, counseling aimed at improving self-efficacy towards exercise and even acquiring a dog to increase walking time. In this narrative review, we aim to examine some traditional and novel barriers to exercise, as well as present evidence on novel interventions or solutions to overcome barriers to increase exercise and physical activity in all people with prediabetes and T2D.